The effects of light emitting diodes on mitochondrial function and cellular viability of M-1 cell and mouse CD1 brain cortex neurons. - Jong Soo Lee; Hyun Jin Park; Sang Ook Kang; Sang Hak Lee; Chang Kyu Lee (PLoS ONE)
The invention of Light Emitting Diode (LED) revolutionized energy-efficient illumination, but concerns persist regarding the potential harm of blue light to our eyes. In this study, we scrutinized the impact of LED light characteristics on eyes using two cell types: M-1 (rich in mitochondria) and CD-1 (neuronal). Variations in color rendering index (CRI) and correlated color temperature (CCT) were investigated, alongside exposure durations ranging from 0 to 24 hours. The findings illuminated the potential benefits of high-quality LED lighting, characterized by a high CRI and low CCT, which emits a greater proportion of red light. This form of lighting was associated with enhanced cell proliferation, elevated ATP levels, and reduced oxidative stress. In contrast, LEDs with low CRI and high CCT exhibited adverse effects, diminishing cell viability and increasing oxidative stress. These results suggest that high-quality LED lighting may have neuroprotective potential as a treatment option, such as for retinal ganglion cells.